Inventory of Ferns (Class: Filicinae) in West Block, Batang Toru Forest, North Tapanuli North Sumatra - Pasaribu, Nursahara (International Journal of Ecophysiology, 2022)
Batang Toru Forest is one of the conservation areas in North Sumatra which has a diversity of flora and fauna, one of which is ferns. A study on ferns in the Batang Toru Forest area has never been carried out, so the species diversity and distribution are unknown. Ferns are classified into 4 classes, one of which is the Filicinae class. The class Filicinae is a group of ferns that has the highest number of species. This study aims to inventory the class Filicinae ferns in the Batang Toru Forest area by using the exploration method, namely exploring along the track. Found 52 species of ferns belonging to 14 families and 29 genera. Of the 52 species found, 33 species were classified as terrestrial ferns and 19 types of epiphytic ferns.